Corporate Value Impact Of Financial Management Policies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purpose of this study was to determine the impact of financial management policies on firm value in the Automotive and Components sub-sector. Financial management policies in this study consist of investment decisions, measuring indicators using Price Earning Ratio, funding decisions using debt to equity ratios, dividend policies using dividend payout ratios and Price to Book Value as indicators of measuring firm value. This study uses panel data analysis which is a combination of periodic data and individual data. By using purposive sampling method, the total sample is 8 companies in the automotive and components sub-sector. Hypothesis testing is done by partially testing the effect of Price Earning Ratio, Debt to Equity Ratio and dividend payout ratios on firm value. The results of the study stated that Price Earning Ratio has a negative and insignificant effect on firm value, Debt to Equity Ratio has a negative and significant effect on firm value and Dividend Payout Ratio has a positive and significant effect on firm value.